LOCKDOWN IN INTERNATIONAL TRADE A NORMATIVE JURISDICTION BASED ON UNITED NATIONS CONVENTION ON CONTRACTS FOR INTERNATIONAL SALE OF GOODS (CISG) 1980 - Djody Riktian Morajaya; M. Putra Iqbal (Jurnal Ilmiah Mahasiswa Bidang Hukum Kenegaraan, 2022)
Abstract-This research aims to explain the relationship between the rules in the CISG 1980 and the lockdown in relation to international trade during the Covid-19 pandemic. Then also find solutions for parties who experience problems when conducting international trade transactions during the lockdown. The research found that there are no special rules in the CISG that regulate international trade during a pandemic. Besides that, the pandemic cannot be used as an absolute reason for filing an exception. Re-negotiation on the basis of pandemic is a step that the parties can take before bringing it to a dispute resolution forum. It is recommended that CISG issue legal instruments such as legal guides that provide directions to carrying out international sale of goods during this Covid-19 pandemic and the parties should include force majeure or hardship clauses based on matters agreed upon by the parties.Keywords: CISG; Covid-19 pandemic; lockdown.